Pengaruh Kualitas Pelayanan Service Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan - Sonny Taufan; Afifah Earlene Putri Santoso (KALBISCIENTIA Jurnal Sains dan Teknologi, 2023)
This study aims to examine the effect of service quality on customer loyalty through customer satisfaction at PT Srikandi Diamond Motors Cakung. PT Srikandi Diamond Motors Cakung is a company engaged in the automotive industry for four-wheeled vehicles and is an authorized dealer of Mitsubishi. This study uses a questionnaire method. Meanwhile, the sampling was carried out using a purposive sampling technique on 70 respondents who had performed general services at PT Srikandi Diamond Motors Cakung. Data analysis in this study used the path analysis method with the help of SPSS software as a data processing application. The research results show that: (1) The service quality variable directly has a significant influence on customer satisfaction and has a t count of 4.596 > 1.995. (2) The service quality variable directly has a significant influence on customer loyalty and has a t count of 2.130 > 1.995. (3) The customer satisfaction variable directly has a significant influence on customer loyalty and has a t count of 4.310 > 1.995. (4) There is an indirect and significant effect on the service quality variable on customer loyalty through customer satisfaction, which has a t count of 3.099 > 1.995.